Central nervous system schwannoma, VGLL-fused (EWSR1::VGLL1 fusion) with neuroblastoma-like cell dense areas in the frontal lobe of a young man with schwannomatosis due to a germline LZTR1 mutation - Munoz, David G.; Das, Sunit; Yoon, Ju-Yoon; Siddaway, Robert; Levine, Adrian; Aldape, Kenneth D. (Free Neuropathology, 2026)
We report a central nervous system schwannoma, VGLL-fused in a young man’s frontal lobe. Somatic abnormalities included an EWSR1::VGLL1 fusion, which incorporated the entire translated region of VGLL1, but excluded most domains of EWSR1. The tumor histologically merged with the brain, and showed both schwannoma-like and neuroblastoma-like areas. A germline LZTR1 mutation was subsequently identified, implying the patient suffered from schwannomatosis.